2021
DOI: 10.1007/s00167-021-06559-y
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental knee arthroplasty: the Italian version of the Forgotten Joint Score-12 is valid and reliable to assess prosthesis awareness

Abstract: Purpose Unicompartmental Knee Arthroplasty (UKA) recorded an increased incidence of around 30% per year in the United States. Patient's experience and satisfaction after surgery were traditionally assessed by pre, and post-surgical scores and Patient-Reported Outcome Measures (PROMs) scales. Traditional scales as Western Ontario and McMaster University Osteoarthritis Index (WOMAC) and Oxford Knee Score (OKS) reported high ceiling efect. Patients treated by UKA usually perform well; therefore, it is necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The ICC obtained in the current study showed that the scale had a high level of reliability. When the literature was reviewed, the results were seen to be similar to those of the reliability tests performed in knee-hip arthroplasty (Longo et al, 2022; Thompson et al, 2015) and femoroacetabular impingement syndrome (Vermeijden et al, 2021) patient groups, in which the test–retest method was used to measure the reliability of FJS-12. These results of this study demonstrate that the scale is a reliable assessment tool and that the same results will be obtained in the consistent and repeated measurements of the FJS-12 items.…”
Section: Discussionmentioning
confidence: 70%
“…The ICC obtained in the current study showed that the scale had a high level of reliability. When the literature was reviewed, the results were seen to be similar to those of the reliability tests performed in knee-hip arthroplasty (Longo et al, 2022; Thompson et al, 2015) and femoroacetabular impingement syndrome (Vermeijden et al, 2021) patient groups, in which the test–retest method was used to measure the reliability of FJS-12. These results of this study demonstrate that the scale is a reliable assessment tool and that the same results will be obtained in the consistent and repeated measurements of the FJS-12 items.…”
Section: Discussionmentioning
confidence: 70%
“…The FJS-12 is an outcome questionnaire designed to evaluate joint awareness [16]. It was translated and validated in the Italian language [17]. This survey consists of 12 questions with a five-point Likert response format that is summed to obtain scores ranging from 12 to 60 [16].…”
Section: Postoperative Scoresmentioning
confidence: 99%
“…19,20 Improving data collection efficiency, allows surgeons and researchers in the US to consider multi-institutional and multi-national collaboration not only to learn from institutions who routinely utilize PROMs, but also to obtain more cultural and linguistically validated instruments for patients in the US. [21][22][23][24][25] The implementation of PROMs has evolved to include mobile health technology and direct integration into the electronic health record. As technology evolves, we must consider who has access to mobile health technology and how to use this technology as a tool to capture PROs.…”
Section: Future Directionsmentioning
confidence: 99%